2001
DOI: 10.5326/15473317-37-4-349
|View full text |Cite
|
Sign up to set email alerts
|

Elevated parathyroid hormone-related protein and hypercalcemia in two dogs with schistosomiasis

Abstract: Two adult dogs were evaluated for hypercalcemia. Diagnostic evaluation identified elevated parathyroid hormone-related protein (PTHrP) and presumptive humoral hypercalcemia of malignancy. At necropsy, schistosomiasis was diagnosed. North American schistosomiasis is caused by Heterobilharzia americana. Clinical findings may include dermatitis, coughing, diarrhea, and anorexia. Clinicopathological findings may include hypercalcemia, hyperglobulinemia, hypoalbuminemia, anemia, and eosinophilia. Diagnosis by fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 29 publications
2
45
1
Order By: Relevance
“…This may explain why the elevation of PTH level is due to the impaired liver function rather than secondary hyperparathyroidism [33] . Moreover, elevated PTH-related protein was obser ved with hyperglobulinemia and hypoalbuminemia in dogs with schistosomiasis [35] , and this may explain the obtained positive correlation between PTH and serum total protein levels in patients with HCV infection due to hyperglobulinemia observed in our study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This may explain why the elevation of PTH level is due to the impaired liver function rather than secondary hyperparathyroidism [33] . Moreover, elevated PTH-related protein was obser ved with hyperglobulinemia and hypoalbuminemia in dogs with schistosomiasis [35] , and this may explain the obtained positive correlation between PTH and serum total protein levels in patients with HCV infection due to hyperglobulinemia observed in our study.…”
Section: Discussionsupporting
confidence: 70%
“…In hepatocellular dysfunction some previous studies reported that serum PTH level is high in patients with primar y biliar y cirrhosis [32] , liver cirrhosis [33] , HBV infection [34] , as well as in dogs with schistosomiasis [35] and in children with cholestatic and non-cholestatic liver disease [36] . On the other hand, other studies reported that PTH is unchanged in patients with chronic viral liver disease [37] and post hepatic cirrhosis [38] .…”
Section: Discussionmentioning
confidence: 99%
“…However, in this noninfectious model, liver function was normal in SCW animals with granulomatous livers and remained unchanged with PTHrP antibody treatment (data not shown). Growing evidence suggests that PTHrP may be involved in the pathogenesis of multiple types of granulomatous disorders, because its increased expression has now been documented in sarcoidosis, schistosomiasis, giant cell granulomas, and idiopathic systemic granulomatous disease (47)(48)(49)(50). However, to our knowledge, the results presented here are the first to identify a function for PTHrP in this pathologic process.…”
Section: Discussioncontrasting
confidence: 47%
“…Intense chronic granulomatous inflammation and fibrosis are usually associated with schistosome ova within tissues. 8,11,13,19,24 However, an association between canine schistosomiasis and lymphosarcoma has not been described.…”
mentioning
confidence: 99%
“…2,19 Clinical signs of canine schistosomiasis may include lethargy, weight loss, anorexia, diarrhea, vomiting, polyuria, and polydipsia; reported clinicopathologic abnormalities include hypercalcemia, hyperglobulinemia, anemia, and eosinophilia. 8,11,13,18,19,24 In infected dogs, adult schistosoma inhabit and lay eggs in the mesenteric venules. The released ova migrate out of the blood vessel and through the intestinal wall to the intestinal lumen or are spread hematogenously to other tissues, primarily the liver.…”
mentioning
confidence: 99%